Prevalence of hypertension and associated factors among residents of Ibadan North Local Government Area of Nigeria (2017)
Background: Hypertension is a major public health challenge worldwide. It is the most important risk factor for cardiovascular disease. Objectives: This study aimed to investigate the prevalence of hypertension and associated factors among the residents of Yemetu community in Ibadan-North Local Government Area of Oyo State, Nigeria. Methods: A descriptive cross-sectional design was used. The study involved 806 respondents aged from 18-90 years from 171 households, selected by cluster sampling technique. It was a house-to-house survey. Behavioural risk factors were measured using World Health Organisation (WHO) STEPwise approach to chronic disease risk factor surveillance (STEPS 1 & 2). Hypertension was defined as Systolic blood pressure (SBP) ≥ 140 and/or Diastolic blood pressure (DBP) ≥ 90mm Hg or currently on anti-hypertensive medication. Data were analysed using descriptive statistics, Chi-square and binary logistic regression tests at P <0.05. Results: The overall prevalence of hypertension was 33.1% (male 36.8% and female 31.1%). The proportion of self reported hypertension was 11.1%, while 5.1% were currently on anti-hypertensive medication. The mean age of the respondents was 38.8 ±15.6 years. The body mass index of the respondents was 5.2%, 52.0%, 29.5% and 13.3% for underweight, normal, overweight and obese, respectively. Alcohol and tobacco use were found in 11.5% and 3.2%, respectively. The result of binary logistic regression analysis revealed that hypertension was significantly associated with being in age groups 30-49 years (OR 2.258, 95% CI: 1.311 - 3.884), ≥50 years (OR 7.145, 95% CI: 3.644 - 14.011), being overweight or obese (OR 2.281, 95% CI: 1.022 – 5.088). Hypertension was inversely associated with being underweight (OR 0.537, 95% CI: 0.395 – 0.832). Conclusion: This study revealed a high prevalence of hypertension. These data underscores the need for urgent steps to create awareness and implement interventions for prevention and early detection of hypertension, especially among those aged ≥30 years and the overweight or obese. "